2017
DOI: 10.1371/journal.pone.0183529
|View full text |Cite
|
Sign up to set email alerts
|

The extremely divergent maternally- and paternally-transmitted mitochondrial genomes are co-expressed in somatic tissues of two freshwater mussel species with doubly uniparental inheritance of mtDNA

Abstract: Freshwater mussel species with doubly uniparental inheritance (DUI) of mtDNA are unique because they are naturally heteroplasmic for two extremely divergent mtDNAs with ~50% amino acid differences for protein-coding genes. The paternally-transmitted mtDNA (or M mtDNA) clearly functions in sperm in these species, but it is still unknown whether it is transcribed when present in male or female soma. In the present study, we used PCR and RT-PCR to detect the presence and expression of the M mtDNA in male and fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 36 publications
(77 reference statements)
2
24
0
Order By: Relevance
“…In recent years, the vision of selective neutrality of mtDNA has been challenged, and our results add to the growing body of evidence showing that cytoplasmic genetic variation can influence fitness [2,6,7,12,14]. They are also in line with the Father's curse hypothesis [30], as DUI allows selection to act directly on the M-mtDNA, which can accumulate mutations that are beneficial or neutral in sperm, but potentially harmful when present and expressed in somatic tissues or in eggs. Since the OXPHOS capacity in heteroplasmic Mytilus male gills does not digress much from homoplasmic female gills, it is plausible that the amount of M-mtDNA does not reach the threshold required to produce a strong effect in male soma [39].…”
Section: (B) Intraspecific Analysessupporting
confidence: 72%
See 2 more Smart Citations
“…In recent years, the vision of selective neutrality of mtDNA has been challenged, and our results add to the growing body of evidence showing that cytoplasmic genetic variation can influence fitness [2,6,7,12,14]. They are also in line with the Father's curse hypothesis [30], as DUI allows selection to act directly on the M-mtDNA, which can accumulate mutations that are beneficial or neutral in sperm, but potentially harmful when present and expressed in somatic tissues or in eggs. Since the OXPHOS capacity in heteroplasmic Mytilus male gills does not digress much from homoplasmic female gills, it is plausible that the amount of M-mtDNA does not reach the threshold required to produce a strong effect in male soma [39].…”
Section: (B) Intraspecific Analysessupporting
confidence: 72%
“…As mentioned above, in these species, females are usually homoplasmic, whereas males possess sperm with paternal mitochondria and soma with maternal mitochondria [27]. That said, some studies have also shown that both parental haplotypes can coexist and be expressed in somatic tissues, mostly in male individuals [30]. In M. edulis, the genetic divergence between the two parental haplotypes reaches 10 -22% [27 -29], whereas it reaches 8% in A. islandica [38].…”
Section: (B) Intraspecific Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…An even more extreme departure from the norm in bivalve mitochondrial genomes is their mode of doubly uniparental inheritance (DUI) -both egg and sperm mitochondria are transmitted from generation to generation in several bivalve species, but only male offspring retain paternally-transmitted mitochondria (with male or M mtDNA) in their gametes [10][11][12] . Adult females of DUI-exhibiting species usually possess only the female-transmitted mtDNA (F mtDNA) in their soma and gametes whereas males possess F mtDNA in their soma and M mtDNA in their gametes [10][11][12][13] . The DNA divergence between F and M mtDNAs usually vary from about 8% to 40% depending on the species 12,14 .…”
mentioning
confidence: 99%
“…One factor explaining this observation may be that the M genome is subject to weaker selective pressures than the F genome due to an unequal "division of labor" in the DUI system 16 . Typical animal mtDNA functions in gonads and somatic tissues of both sexes whereas under DUI, F mtDNA functions in female gonads and the soma of both sexes, while M mtDNAs functions primarily in spermatozoa of male gonads and only partially in the male soma 13,16,18 . As opposed to SMI that promotes homoplasmy, a state in which all mtDNA copies are typically genetically identical in each cell, thus preventing potentially harmful genomic conflicts, DUI is a naturally heteroplasmic system in which two highly divergent mitochondrial lineages coexist in the same nuclear background, enabling the analysis of the consequences of tissue heteroplamy 13 .…”
mentioning
confidence: 99%